The Complete Artistic Self: Five Collaborators Talk about Barbara Hannigan - Majeau-Bettez, Emanuelle (Circuit, 2020)
Who is Barbara Hannigan, as a singer, performer, conductor, mentor, and community-involved musician? What is the impact of her personality on the music scene? How has her artistic character evolved throughout her formative and professional years? With these questions in mind, I interviewed five of Hannigan’s closest, and most important collaborators and mentors: Hans Abrahamsen, George Benjamin, Gary Kulesha, Mary Morrison and Thomas Morris. Individually, the interviews shed light on specific phases and events in Hannigan’s career, from her undergraduate studies to the present. Taken as a whole, they open the door to understanding Barbara Hannigan as a complete—and completely fearless—artist.